Recycling Used-Coffee Grounds into Hierarchical Nanostructured Carbon for Supercapacitor Application - Rajasekar, C.; Ranjitha, M. Roselin; Kumar, K. Thileep; Kalaivani, RA.; Raghu, S. (Asian Journal of Chemistry, 2023)
Hierarchical nanostructured activated carbon electrode material was prepared from the used-coffee grounds to fabricate a cost-effective, scalable and high-performance symmetric supercapacitor. The interconnected, disordered and microporous material was synthesized in a simple two-stage method of chemical activation with zinc chloride followed by direct pyrolysis of the coffee grounds at 900 ºC in nitrogen atmosphere. The N2 adsorption and desorption analysis showed that the prepared material had an extraordinary surface area of 1178 m2 g-1. The fabricated symmetric supercapacitor device in non-aqueous tetraethylammonium tetrafluoroborate (TEABF4) electrolyte exhibited 2.7 V cell voltage with superior specific capacitance, energy and power density of 129 F g–1, 56.4 Wh kg–1 and 797.9 W kg–1, respectively. Besides, it also had a high specific capacitance retention of 99% even after 10,000 cycles. This work demonstrated an effective approach to transform coffee grounds into high performance electrode material for renewable energy devices. The observed electrochemical performance evidently showed that the materials derived from waste coffee grounds could be recycled into potential electrode material for supercapacitors. The cost-effectiveness and abundance of waste coffee grounds combined with the simple activation process and high performance of the synthesized material increased its feasibility for commercial applications in energy storage devices.